2008
DOI: 10.5253/078.096.0117
|View full text |Cite
|
Sign up to set email alerts
|

Dominance Relationships in Dark-Bellied Brent GeeseBranta bernicla berniclaat Spring Staging Areas

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…This suggests that a combination of juvenile condition, competition, and dominance in flocks may influence the persistence of goose family bonds (Johnson and Raveling 1988;Jónsson and Afton 2008). Family size decrease and family dissolution, i.e., the loss of some or all juveniles, have been linked to the onset of spring (Prevett and Mac-Innes 1980;Johnson and Raveling 1988;Black and Owen 1989), increased levels of parental aggression toward juveniles (Black and Owen 1989;Poisbleau et al 2008;Scheiber et al 2013) and the higher exposure of families to hunting (Madsen et al 2002;Madsen 2010;Guillemain et al 2013;Clausen et al 2017). Still, accidental events, such as the separation of geese from their families during chaotic flock take-offs cannot be ruled out (Prevett and MacInnes 1980).…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that a combination of juvenile condition, competition, and dominance in flocks may influence the persistence of goose family bonds (Johnson and Raveling 1988;Jónsson and Afton 2008). Family size decrease and family dissolution, i.e., the loss of some or all juveniles, have been linked to the onset of spring (Prevett and Mac-Innes 1980;Johnson and Raveling 1988;Black and Owen 1989), increased levels of parental aggression toward juveniles (Black and Owen 1989;Poisbleau et al 2008;Scheiber et al 2013) and the higher exposure of families to hunting (Madsen et al 2002;Madsen 2010;Guillemain et al 2013;Clausen et al 2017). Still, accidental events, such as the separation of geese from their families during chaotic flock take-offs cannot be ruled out (Prevett and MacInnes 1980).…”
Section: Introductionmentioning
confidence: 99%
“…In geese, sex, age, mating status (paired or single) and reproductive success (number of juveniles) have been found to be variously related to dominance status (e.g. Lamprecht 1986b;Black and Owen 1987;Stahl et al 2001;Poisbleau et al 2006aPoisbleau et al , 2008. Stahl et al (2001) found that social dominance increased with age for female Barnacle Geese Branta leucopsis whereas it was less obvious for males in a group of non-breeding moulting individuals.…”
Section: Introductionmentioning
confidence: 99%